Dietary exposure and risk assessment of polychlorinated dibenzo-p-dioxins, polychlorinated dibenzofurans and dioxin-like polychlorinated biphenyls of the population in the Region of Valencia (Spain). Issue 4 (3rd April 2018) - Quijano, Leyre; Marín, Silvia; Millan, Encarnación; Yusà, Vicent; Font, Guillermina; Pardo, Olga
ABSTRACT: Dietary exposure of the Valencia Region population to polychlorinated dibenzo- p -dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and PCBs was assessed in the Region of Valencia in 2010–2011. A total of 7700 food samples were collected. Occurrence data were combined with consumption data to estimate dietary exposure in adults (>15 years of age) and young people (6–15 years of age). The estimated intake was calculated by a probabilistic approach. Average intake levels (upper-bound scenario) were 1.58 and 2.76 pg toxic equivalent (TEQ) kg −1 body weight (bw) day −1 for adults and young people, respectively. These average intakes are within range of the tolerable daily intake of 1–4 pg WHO-TEQ kg −1 bw day −1 recommended by WHO, and slightly above the tolerable weekly intake (TWI) of 14 pg TEQ kg −1 bw week −1 and the Provisional tolerable monthly intake of 70 pg TEQ kg −1 bw month −1 set by the Scientific Committee on Food and the Joint FAO/WHO Expert Committee on Food, respectively. These results show that the contamination levels in food and therefore the exposure of the general population to PCDD/Fs and PCBs have declined in this region and therefore show the efficiency of the European risk-management measures. In terms of risk characterisation, the results showed that, under the upper-bound scenario, 22% of the adult and 58% of the young people population could exceed the TWI.